The Impact of Peer Interaction and Gadget Addiction on the Subjective Wellbeing of 5–6-Year-Old Children in Java, Indonesia: A Quantitative Study - Saroinsong, W.P; Nursalim, M; Azmawaty Binti Mohamad Nor (G-Couns: Jurnal Bimbingan dan Konseling, 2025)
The advancement of digital technology has altered children's social interactions, particularly in Indonesia, where early gadget use may limit direct peer contact and impede social-emotional development. Although positive peer relationships are essential for children's subjective well-being, studies examining the link between gadget addiction, peer interaction, and well-being in early childhood within a local cultural context are still scarce. This quantitative study surveyed 400 children aged 5–6 years in Java, Indonesia, using questionnaires on peer relationships, gadget addiction, and well-being. Multiple linear regression and path analysis revealed that peer interaction significantly influences subjective well-being (β = 0.362, p < 0.001), while gadget addiction was not directly significant (β = 0.013, p = 0.165). Gadget use, however, served as a mediating variable. These findings emphasize the importance of promoting strong peer interactions and managing screen exposure to support emotional and social development in early childhood. Keywords: peers; children, subjective well-being, gadget addiction